GSK-3β at the Intersection of Neuronal Plasticity and Neurodegeneration - Tomasz Jaworski; Ewa Banach-Kasper; Katarzyna Gralec (Neural Plasticity)
In neurons, Glycogen Synthase Kinase-3β (GSK-3β) has been shown to regulate various critical processes underlying structural and functional synaptic plasticity. Mouse models with neuron-selective expression or deletion of GSK-3β present behavioral and cognitive abnormalities, positioning this protein kinase as a key signaling molecule in normal brain functioning. Furthermore, mouse models with defective GSK-3β activity display distinct structural and behavioral abnormalities, which model some aspects of different neurological and neuropsychiatric disorders. Equalizing GSK-3β activity in these mouse models by genetic or pharmacological interventions is able to rescue some of these abnormalities. Thus, GSK-3β is a relevant therapeutic target for the treatment of many brain disorders. Here, we provide an overview of how GSK-3β is regulated in physiological synaptic plasticity and how aberrant GSK-3β activity contributes to the development of dysfunctional synaptic plasticity in neuropsychiatric and neurodegenerative disorders.